Recognition of Lipopolysaccharide and Activation of NF-κB by Cytosolic Sensor NOD1 in Teleost Fish - Bi, Dekun; Wang, Yue; Gao, Yunhang; Li, Xincang; Chu, Qing; Cui, Junxia; Xu, Tianjun (Frontiers in Immunology, 2018)
Lipopolysaccharide (LPS) is the major component of the outer membrane of Gram-negative bacteria. This molecule can induce strong immune response and various biological effects. In mammals, TLR4 can recognize LPS and induce inflammatory response. However, the innate receptor in fish for recognizing LPS remains ambiguous. LPS can invade the cytoplasm via Gram-negative bacteria outer membrane vesicles and detected by intracellular receptor caspase-11 in mammals, so, there was may also exist the intracellular receptors that can recognize LPS in fish. NOD1 is a member of NOD-like receptors family and can recognize the iE-DAP in the cytoplasm in mammals. In fish, NOD1 also can respond to infection of Gram-negative bacteria and may play an important role in the identification of bacterial components. In this study, to study whether NOD1 is a recognition receptor for LPS, we detected the expression of NOD1 and several cytokines at transcript levels to determine LPS can induce inflammatory response in teleost fish and NOD1 can respond to LPS. Then we perform the binding analysis between NOD1 and ultrapure LPS by using Streptavidin pulldown assay and ELISA assay to prove NOD1 can be combined with LPS, and using dual luciferase reporter gene assay to verify the signal pathways activated by NOD1. Next, through cell viability analysis we proved that LPS-induced cytotoxicity can mediated by NOD1 in fish. The results showed that NOD1 can identify LPS and activate the NF-κB signal pathway by recruiting RIPK2 and then promoting the expression of inflammatory cytokines to induce the resistance of an organism against bacterial infection.